THE IMPLEMENTATION OF PEER MENTORING PROGRAM AT THE ENGLISH DEPARTMENT OF SRIWIJAYA STATE POLYTECHNIC - Tiur Simanjuntak (Politeknik Negeri Sriwijaya, 2013)
The aim of this study is to evaluate peer mentoring program being implemented at English Department. Some problems are identified in this study such as how it is implemented, challenges faced, and student’s perception on this program. Interviews, observation and document review are done in the area of mentoring covering concept, mentoring characteristics, its advantages and disadvantages. The result shows that students give positive feedback to this program such as the increase of students’ engagement, academic atmosphere, communication skill and service learning. The atmosphere then motivates students to study among themselves which improve not only their intellectual ability but also their soft skill including communication, leadership and teamwork. While implementing the program, some challenges factors such as inexperienced mentors and time management makes the team not run smoothly.